2021
DOI: 10.1093/cvr/cvab269
|View full text |Cite
|
Sign up to set email alerts
|

EDIL3 deficiency ameliorates adverse cardiac remodelling by neutrophil extracellular traps (NET)-mediated macrophage polarization

Abstract: Aims After myocardial infarction (MI), injured cardiomyocytes recruit neutrophils and monocytes/macrophages to myocardium, which in turn initiates inflammatory and reparative cascades, respectively. Either insufficient or excessive inflammation impairs cardiac healing. As an endogenous inhibitor of neutrophil adhesion, EDIL3 plays a crucial role in inflammatory regulation. However, the role of EDIL3 in MI remains obscure. We aimed to define the role of EDIL3 in cardiac remodeling after MI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 71 publications
1
31
0
Order By: Relevance
“…In a pig model of cardiac ischemia induced by left circumflex artery ligation, DEL-1 treatment improved cardiac function [107]. Wei et al found that DEL-1 levels were decreased in severe AMI patients, which is consistent with WT mice following MI showing low levels of cardiac DEL-1 [42]. Compared with WT mice, DEL-1 -/mice showed significantly improved cardiac function and alleviated cardiac remodeling post-MI.…”
Section: Ischemic Heart Diseasementioning
confidence: 76%
See 3 more Smart Citations
“…In a pig model of cardiac ischemia induced by left circumflex artery ligation, DEL-1 treatment improved cardiac function [107]. Wei et al found that DEL-1 levels were decreased in severe AMI patients, which is consistent with WT mice following MI showing low levels of cardiac DEL-1 [42]. Compared with WT mice, DEL-1 -/mice showed significantly improved cardiac function and alleviated cardiac remodeling post-MI.…”
Section: Ischemic Heart Diseasementioning
confidence: 76%
“…The study by Wei et al is the only report of amelioration of DEL-1 deficiency [42]. In previous reports, inhibition of neutrophil recruitment improved cardiac dysfunction and cardiac remodeling after MI [114][115][116].…”
Section: Ischemic Heart Diseasementioning
confidence: 94%
See 2 more Smart Citations
“…Furthermore, NETs also play a significant role in atherosclerosis disease [ 13 ]. A study has confirmed that deficiency of EGF-like repeats and discoidin I-like domain 3 can improve adverse cardiac healing through polarization of pro-inflammatory macrophage which is mediated by NETs [ 14 ]. In particular, NETs are even associated with preeclampsia and central nervous system diseases [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%